Holocene slip rates along the San Andreas Fault System in the San Gorgonio Pass and implications for large earthquakes in southern California. Issue 11 (9th June 2017) - Heermance, Richard V.; Yule, Doug
Abstract: The San Gorgonio Pass (SGP) in southern California contains a 40 km long region of structural complexity where the San Andreas Fault (SAF) bifurcates into a series of oblique‐slip faults with unknown slip history. We combine new 10 Be exposure ages (Qt4: 8600 (+2100, −2200) and Qt3: 5700 (+1400, −1900) years B.P.) and a radiocarbon age (1260 ± 60 years B.P.) from late Holocene terraces with scarp displacement of these surfaces to document a Holocene slip rate of 5.7 (+2.7, −1.5) mm/yr combined across two faults. Our preferred slip rate is 37–49% of the average slip rates along the SAF outside the SGP (i.e., Coachella Valley and San Bernardino sections) and implies that strain is transferred off the SAF in this area. Earthquakes here most likely occur in very large, throughgoing SAF events at a lower recurrence than elsewhere on the SAF, so that only approximately one third of SAF ruptures penetrate or originate in the pass. Plain Language Summary: How large are earthquakes on the southern San Andreas Fault? The answer to this question depends on whether or not the earthquake is contained only along individual fault sections, such as the Coachella Valley section north of Palm Springs, or the rupture crosses multiple sections including the area through the San Gorgonio Pass. We have determined the age and offset of faulted stream deposits within the San Gorgonio Pass to document slip rates of these faults over the last 10, 000 years. Our results indicate a long‐term slip rate of 6 mm/yr, which is almost 1/2 of the rates east and west of this area. These new rates, combined with faulted geomorphic surfaces, imply that large magnitude earthquakes must occasionally rupture a 300 km length of the San Andreas Fault from the Salton Sea to the Mojave Desert. Although many ( 65%) earthquakes along the southern San Andreas Fault likely do not rupture through the pass, our new results suggest that large > M w 7.5 earthquakes are possible on the southern San Andreas Fault and likely occur every 1000–1500 years. Key Points: New 10 Be cosmogenic exposure ages from Holocene fan surfaces in the San Gorgonio Pass, CA Fault scarps imply Holocene slip rates of 5.7 mm/yr across the San Andreas Fault System Thirty‐seven to Forty‐nine percent of San Andreas slip goes through San Gorgonio Pass, suggesting that some, but not all, earthquakes may penetrate this region